Proteomic insights into COPD pathogenesis and therapeutic targets: a causal analysis of circulating proteins - Luo, Min; Tang, Ying; Qiu, Jing; Yang, Kai; Dai, WenJing; Fang, EnRong (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a preventable and treatable condition, yet current therapies do not halt disease progression, highlighting the need for novel treatments. Using an integrated approach combining proteome-wide Mendelian randomization and Bayesian colocalization analysis, this study identifies novel therapeutic targets for COPD. This study explores causal links between circulating proteins and COPD, identifies potential drug targets, and examines the role of lifestyle factors.MethodsUsing a large proteomics database and a public dataset of 394,244 samples (21,617 COPD cases and 372,627 controls), 4,907 proteins were associated with COPD. Causality was assessed using Bayesian colocalization and proteome-wide Mendelian Randomization (MR), and protein–protein interactions were mapped via STRING. Therapeutic potential was evaluated by identifying drug targets. Additionally, plasma protein expression validation was performed using Western blot experiments in recruited COPD patients and healthy controls.ResultsMR identified 18 proteins linked to COPD, with 11 accelerating disease onset. Strong colocalization evidence was found for MMP12, ASM, KLC1, NPNT and SNX1, none of which overlap with current COPD drug targets. Western blot analysis validated these findings in plasma samples, showing significantly increased expression of MMP12 and ASM, and decreased expression of NPNT and SNX1 in COPD patients compared to healthy controls, while KLC1 showed no significant difference. Notably, MMP12 was negatively associated with grain and nut intake and positively correlated with smoking (p < 0.05).ConclusionThis study identifies potential treatment targets and provides evidence linking specific plasma proteins to COPD risk. Additionally, lifestyle changes may modulate key proteins affecting COPD risk. These findings suggest new avenues for COPD prevention and treatment strategies.